The frontiers of the Melayu world (Malaysia, 1998)
It is thus my aim here to depict the environment and transformation of the wetlands and the natural history of the culture there,...
Keywords: Coastal ecology,Wetland ecology,Wetland conservation,Sinh thái ven biển; Melayu,Melayu,Melayu